First-generation BNT162b2 and AZD1222 vaccines protect from COVID-19 pneumonia during the Omicron variant emergence. (June 2022) - Murillo-Zamora, E.; Trujillo, X.; Huerta, M.; Ríos-Silva, M.; Lugo-Radillo, A.; Baltazar-Rodríguez, L.M.; Mendoza-Cano, O.
Abstract: Objective: This study aimed to identify factors predicting pneumonia in adults with coronavirus disease 2019 (COVID-19) during the Omicron variant (B.1.1.529) emergence. We also evaluated, in fully vaccinated (BNT162b2 or AZD1222) individuals, if the time (<6 or ≥6 months) elapsed since the last shot was received was associated with the risk of severe illness. Study design: A retrospective cohort study was conducted in Mexico. Methods: Data from 409, 493 were analyzed, and risk ratios (RRs) and 95% confidence intervals (CIs) were computed through generalized linear models. Results: We documented a total of 3513 COVID-19 pneumonia cases (69.5 per 100, 000 person-days). In multiple analyses, a protective effect was observed in vaccinated adults (RR = 0.996, 95% CI 0.995–0.997). Male gender, increasing age, and smoking were associated with a greater risk of pneumonia. Individuals with chronic comorbidities (pulmonary obstructive disease, type 2 diabetes mellitus, arterial hypertension, kidney disease, and immunosuppression) were also at higher risk. Among fully vaccinated subjects ( n = 166, 869), those who had received the last shot at 6 more months were at increased risk for developing pneumonia (RR = 1.002, 95% CI 1.001–1.003). Conclusions: Our results suggest that the first-generation BNT162b2 and AZD1222 vaccines reduce the risk of COVID-19 pneumonia during the Omicron emergence. We also found that adults with longer interval from the administration of the second shot to illness onset were at increased risk of severe manifestations.